Mutation of the d-hordein gene by RNA-guided Cas9 targeted editing reducing the grain size and changing grain compositions in barley. (1st May 2020) - Yang, Qiang; Zhong, Xiaojuan; Li, Qing; Lan, Jinyu; Tang, Huaping; Qi, Pengfei; Ma, Jian; Wang, Jirui; Chen, Guoyue; Pu, Zhien; Li, Wei; Lan, Xiujin; et al.
Highlights: d -Hordein of barley was knock out using RNA-guided Cas9 without any off-target mutations. Homozygous mutant and transgene-free plants were obtained by segregation in selfing populations of edited lines. The mutant grain morphology changed, prolamines reduced, glutenins increased, and changes of other grain composition. Abstract: In this study, we successfully knock-out the d -hordein component of barley storage protein using RNA-guided Cas9. Mutation frequencies of 25% and 14% at two different target sites were obtained. Homozygous mutant plants that were T -DNA free were identified in the T1 generation. Barley grains without d -hordein proteins from T2 seeds showed a significantly reduced grain size compared to the parent plant and control non-edited line. The protein matrix surrounding the starch granules was increased, whereas the starch granules themselves were decreased in size in the mutant plants compared to controls. The main effect of a lack of d -hordein was a considerable decrease in the prolamines and an increase in the glutenins. The changes of other grain composition included the increased starch content, amylose content, and β-glucan content. The roles of d -hordein mutation on barley grain size and grain composition remain to be studied.